Exploring the RC-106 Chemical Space: Design and Synthesis of Novel (E)-1-(3-Arylbut-2-en-1-yl)-4-(Substituted) Piperazine Derivatives as Potential Anticancer Agents - Listro, Roberta; Stotani, Silvia; Rossino, Giacomo; Rui, Marta; Malacrida, Alessio; Cavaletti, Guido; Cortesi, Michela; Arienti, Chiara; Tesei, Anna; Rossi, Daniela; Giacomo, Marcello Di; Miloso, Mariarosaria; et al. (Frontiers in Chemistry, 2020)
Despite significant advances in treatment of common cancers have been achieved over the years, orphan tumors still represent an important unmet medical need. Due to their complex multifactorial origin and limited number of cases, such pathologies often have very limited treatment options and poor prognosis. In the search for new anticancer agents, our group recently identified RC-106, a Sigma Receptor modulator endowed with proteasome inhibition activity. This compound showed antiproliferative activity towards different cancer cell lines, among them glioblastoma (GB) and multiple myeloma (MM), two currently unmet medical conditions. In this work, we directed our efforts toward the exploration of chemical space around RC-106 to identify new active compounds potentially useful in cancer treatment. Thanks to a combinatorial approach, we prepared 41 derivatives of the compound, and evaluated their cytotoxic potential against MM and GB. Three novel potential anticancer agents have been identified.